Classification for ammonia in water by specific concentration using artificial neural network (ANN) - Muhamad Faruqi, Zahari; M. S., Najib; Suhaimi, Mohd Daud; Mujahid, Mohamad; Suziyanti, Zaib
Water pollution caused by poor management of waste water release or dump need to be monitored. This paper present to monitor on ammonia release by industry which can caused death to plant worker. This monitoring was a combination between E-Nose and Classification techniques which is ANN. ANN the most common retrieval method that used in industry nowadays. Furthermore, ANN classification successful to classify 100% accuracy for specific concentration of Ammonia which is using Lavernberg-Marquardt (LM) algorithm with supervised learning and fast convergence Back Propagation (BP) method.